Comparing Live and Digital Augmented Reality Models for Demonstrating Two Motor Skills From the Test of Gross Motor Development—Second Edition: TGMD-2. Issue 2 (April 2020) - Spinosa, Rodrigo Martins de Oliveira; Santo, Dalberto Luiz De; Costa, Rafaela Zortéa Fernandes; Pazetto, Nerylson Ferraz; Santos, Camila Ramos dos; Medina-Papst, Josiane; Marques, Inara
The objective of this study was to compare the effect of digital (i.e., augmented reality [AR]) and live demonstrations of two fundamental motor skills. The motor skills were horizontal jump and over-the-shoulder throw with performance criteria described in the Test of Gross Motor Development—Second Edition (TGMD-2). We developed a digital model using AR installed on a tablet computer compatible with the Android operating system. We recruited 131 children and assigned them to three age groups: G1, 3-5 years old ( M = 4.25, SD = 0.71 years); G2, 6-8 years old ( M = 7.16, SD = 0.79 years); and G3, 9-11 years old ( M = 10 .13, SD= 0.84 years). Randomly, half of the children in each group performed the two motor skills after watching either the AR or the live demonstrations; seven days later, all children repeated the motor skills with the demonstration type inverted. We applied Wilcoxon's test with statistical significance set at p < .05 and found no significant performance differences based on demonstration exposure from AR versus live modeling. We propose that AR technology is a potential tool for demonstrating human movement.